Exogenous melatonin boosts vaccine-induced immunity in individuals with high pre-existing influenza immunity - Oda, Kyosuke; Danko, Janine; Villasante, Eileen; Bergmann-Leitner, Elke; Lee, Rachel; Wijayalath, Wathsala (Frontiers in Immunology, 2025)
IntroductionNaturally produced melatonin acts as an antioxidant and immunomodulator, regulating sleep and vital functions. Synthetic melatonin is widely used as a sleep aid by the general population, including U.S. military personnel. Immunomodulatory effects of melatonin on vaccines and therapeutics must be studied to develop and implement effective clinical practice guidelines, which will enhance the quality of life of the public and the military readiness. Here, we evaluated exogenous melatonin mediated immune modulation during seasonal influenza vaccination using the samples generated in the Melatonin and Vaccine Response, Immunity, and Chronobiology Study (MAVRICS) conducted by the Naval Medical Research Command (NMRC) and the Walter Reed National Military Medical Center (WRNMMC).MethodsMAVRICS participants had received quadrivalent inactivated influenza vaccine (IIV4) (2022/23 season) after being randomized to melatonin (REMfresh® 5mg melatonin caplets one hour before the planned bedtime for 14 days, starting on the night of vaccination) or no treatment (control). The hemagglutination inhibition (HAI) antibody responses, serum cytokine/chemokines, and in vitro antigen-specific cellular responses were measured at 24-48h pre-vaccination and 14–21 days post-vaccination. Peripheral blood mononuclear cells were stimulated with recombinant hemagglutinin proteins in vitro to measure antigen-specific responses. For the data analysis, participants were stratified by the baseline HAI titers of the A/Victoria vaccine strain.ResultsVaccination induced a significant increase in HAI antibodies, antigen specific circulating T follicular helper 17 (cTfh17) cells and IL-2, IL-4, IL-17A, IL-13 cytokines in the melatonin recipients who had high HAI baseline titers. These changes were not seen in their control counterparts. The cTfh17 levels remained unchanged and present at consistently high levels in the low HAI baseline melatonin recipients, while both cTfh2 and cTfh17 subsets were increased in those of the control vaccinees. Notably, melatonin itself did not significantly impact the global cytokine milieu in the serum.DiscussionThe data suggest that the melatonin has a selective modulatory effect on the antigen-specific cTfh subset response based on the levels of pre-existing HAI antibodies and the previously imprinted immune landscape. Given the disease’s complex immune history, melatonin shows promise as a potential adjuvant for seasonal influenza vaccines.